Rheological and Microstructural Study of a356 Alloy Solidified Under Magnetic Stirring - Bustos-Castillo, O; Ordonez, S (American Foundry Society, 2013)
Results on the rheological behavior of an A356 alloy compressed between parallel plates in the semisolid state are presented in this work. The tests were performed on cylindrical specimens machined from billets cast while being subjected to a rotating permanent magnetic field. These samples did not exhibit the conventional microstructure of dendrites, and were tested with different solid fractions. The tests were performed either at a constant load or at a constant displacement rate. A power law equation was derived to describe the rheological behavior of the material when tested at constant load, however, it was not possible to establish a mathematical relationship to describe the flow on the semisolid material when the tests were made at constant displacement rate. It can be concluded from these results that the rheological behavior of the alloy is affected by the morphology of the phases present in the microstructure, in such a way that a globular microstructure, with a shape factor near the unit, behaves as a fluid while deformed in the semisolid state, a behavior that is not witnessed in an as-cast dendritic microstructure. Copyright © 2013 American Foundry Society.